PENDAMPINGAN PENULISAN PROPOSAL PENELITIAN KUALITATIF BAGI GURU-GURU DI MADRASAH ISLAMIYAH CIOMAS KABUPATEN SERANG - Suryapermana, Nana; Agustina, Nurmalia; Idris, Muhamad Fadhil (Yayasan Education and Social Center, 2025)
This community service activity aimed to enhance the competencies of teachers at Madrasah Islamiyah Ciomas, Serang Regency, in writing qualitative research proposals. The mentoring was conducted through a series of workshops that provided teachers with a comprehensive understanding of qualitative research concepts and the proper way to write research proposals according to academic standards. Prior to the mentoring, most teachers struggled with understanding qualitative research methodology and structuring research proposals effectively. After the activity, there was a significant improvement in their understanding and skills, evidenced by evaluation results showing more than a 50% increase in every assessed aspect. Furthermore, most teachers successfully developed research proposals that met academic standards. This activity demonstrates that mentoring can positively impact teachers' research skills, which ultimately supports their professional development and the overall quality of education at Madrasah Islamiyah Ciomas